Human rights and consumer education for better quality of life - Mohd Hamdan Adnan (Penerbit UMS, 2016)
In today’s world, knowing our rights as humans and consumers are critical in order to enhance our quality of life and sustain it. Ignorance of our human and consumer rights can subject us to all kinds of continuous exploitations and persecutions. This article tries to make a case on human rights and consumer education as an essential part of the national education curriculum. The article argues that human rights and consumer educations should not be confined to schools but be part of a life-long learning process. Further, it should not be for the ordinary citizens only but also for those in authority, like enforcement officers and managers in the corporate sectors. By everyone understanding human rights and consumer rights it is hope that the world can be a better place, not only through good governance but also justice in the market-place. This is based on the philosophy that the best form of protection is self-protection.